Nietzsche’s Shakespeare: Musicality and Historicity in The Birth of Tragedy - Brennan, Katie (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2014)
Nietzsche was deeply interested in Shakespeare during the period leading up to the publication of The Birth of Tragedy. His notebooks from this period clearly indicate that throughout the planning stages of The Birth of Tragedy, Nietzsche had intended to devote an entire chapter to Shakespeare, in which Shakespeare was to serve as a bridge between the spirit of the great ancient Greek playwrights and Wagner. In this paper I discuss why, despite the absence of a detailed account of Shakespeare in the final version of The Birth of Tragedy, he is nonetheless essential to Nietzsche’s theory of tragedy. Keywords: Nietzsche, Shakespeare, Tragedy, Aesthetics, Hamlet